Ragam Bahasa Indonesia di Media Sosial - Satrya Wibisana Mirza (Simpati, 2023)
Indonesian is the official language of our country, Indonesia. Indonesian as the main community communication element and tool in Indonesia. The development of information technology allows global communication so fast that it means it can reach across countries and across continents. In this discussion "The use of Indonesian in social media is good and correct" many users of this application do not use the correct KBBI language and standard Indonesian grammar. While many causes of errors in the meaning of language. The same is true for the purpose of conducting this research or seeing how much social media use is still wrong in the use of Indonesian. Indonesian is also not used globally, which makes Indonesian seem less useful for the globalization process. Increasing the function as a scientific foundation must be carried out in accordance with the development of science and technology in Indonesia.